Anti-fouling PEDOT conductive polymer enzyme-containing ink material with good conductivity and water solubility and preparation method of anti-fouling PEDOT conductive polymer enzyme-containing ink material
Through zwitterionic functional polymers and oxidative polymerization technology, conductive bioinks with biocompatibility and anti-fouling properties were prepared, which solved the problem of adhesion of inks in the biological environment in the prior art and improved the conductivity and enzyme activity. Maintaining capability, suitable for a variety of bioenzyme sensors.
Patent Information
- Application Number
- CN202411268989.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2024-12-13
AI Technical Summary
In the existing bioelectronic device manufacturing technology, solution-processable inks lack biocompatibility and enzyme activity maintenance capabilities when used, and after molding, the material is prone to nonspecific adhesion in complex biological environments, affecting the conductivity and sensor life. .
Using zwitterionic functionalized poly3,4-ethylenedioxythiophene:polystyrene sulfonate (PEDOT-PC:PSS) polymer, conductive bioink with solution processing properties is prepared by oxidative polymerization, and the crosslinking temperature is regulated and time, a material with excellent conductivity and aqueous phase stability is formed.
The biocompatibility, soil resistance and enzyme activity maintenance of conductive bioinks is achieved, the sensitivity and long-term stability of the sensor are improved, the manufacturing process is simplified, and the cost is reduced.
Smart Images

Figure CN119125273A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of biomaterials, and in particular relates to a conductive bio-ink with solution processability. The material after molding has good conductivity, water phase stability, biocompatibility and anti-fouling properties. Background Art
[0002] In recent years, with the rapid development of bioelectronic science and technology, it has been widely used in disease treatment, health monitoring, personalized medicine, etc. Traditional bioelectronic manufacturing technology, such as photolithography, has become a preparation technology with more bioelectronic applications due to its high precision and mature technology. However, this manufacturing method is costly, which limits its application. Compared with traditional bioelectronic device manufacturing technology, solution processing technologies such as screen printing technology, inkjet printing technology and roll-to-roll processing technology have gradually become the mainstream method for preparing bioelectronic devices with their advantages of low cost, personalized customization and large-scale preparation, showing great potential in the field of bioelectronic device manufacturing. At present, the inks used for solution processing include polymer inks, carbon-based inks, composite inks and metal particle inks, and a variety of bioelectronic devices have been prepared using their electronic conductivity and sensing properties. However, these inks lack good biocompatibility when used and cannot maintain enzyme activity, so they are prepared by layer-by-layer printing. However, this process is time-consuming and inefficient, which reduces the attractiveness of solution processing technology. In addition, after the ink material is printed and formed, it also faces the problem of nonspecific adhesion of its interface in a complex biological environment. This adhesion not only hinders the charge conduction between the material and the analyte, affects the transmission of the signal, and leads to a decline in device performance, but also the enzyme inactivation induced by nonspecific adhesion will lead to reduced sensor sensitivity and shortened life. In the previous work of the research group, conductive polymers with resistance to nonspecific adhesion were prepared by electrochemical polymerization. However, electrochemical polymerization will cause the polymer to be insoluble, making it difficult to process it secondary, unable to be deposited on non-conductive substrates, and difficult to prepare on a large scale. To solve this problem, the research group prepared a soluble conductive polymer with resistance to nonspecific adhesion by chemical oxidation polymerization in the previous work. However, since this conductive polymer has good water solubility, it faces the problem of easy disintegration when used in an aqueous environment and low conductivity. Summary of the invention
[0003] The invention provides a zwitterion functionalized poly (3,4-ethylenedioxythiophene):polystyrene sulfonate (PSS) polymer, which has excellent solution processability and biocompatibility.
[0004] The present invention provides a conductive bio-ink product with solution processability. The ink has excellent solution processability and biocompatibility, and the material after molding has good conductivity, biocompatibility and anti-fouling properties.
[0005] The present invention provides a conductive bio-ink molding preparation method, which can solidify the conductive bio-ink and stably exist in an aqueous environment, and by regulating the cross-linking temperature and cross-linking time, the material after the conductive bio-ink is molded has excellent conductivity and aqueous stability.
[0006] The invention provides a material formed by enzyme-containing conductive bio-ink, which has excellent conductivity, anti-fouling and biocompatibility, can well maintain the activity of enzymes, and can be applied to a variety of enzyme-based sensors.
[0007] As the preferred technical solution:
[0008] (1) Zwitterion functionalized poly (3,4-ethylenedioxythiophene) and polystyrene sulfonate were dissolved in deionized water. Catalyst ferric sulfate and oxidant sodium persulfate were used for oxidative polymerization, and cation exchange resin and anion exchange resin were added to remove impurities. The molar ratio of zwitterion functionalized poly (3,4-ethylenedioxythiophene) to polystyrene sulfonate was 1:0.5-1:3. Among them, phosphorylcholine functionalized poly (3,4-ethylenedioxythiophene) to polystyrene sulfonate (PEDOT-PC:PSS) with a feed ratio of 1:1 had good antifouling performance ( Figure 1 )、Biocompatibility( Figure 2 ) and excellent solution processing properties.
[0009] (2) Mix the zwitterion functionalized poly (3,4-ethylenedioxythiophene): polystyrene sulfonate solution with the additive and wetting agent and stir. The additive concentration is 0.01-0.2 mg mL -1 , and add a volume fraction of 0.01-0.2 mg mL - 1 GOPS was sonicated for 5 min to prepare a conductive bio-ink with solution processability.
[0010] A conductive bio-ink with solution processing performance as described above is characterized by containing at least one of dimethyl sulfoxide (DMSO), ethylene glycol, dimethylformamide, tetrahydrofuran, glycerol, sorbitol, ethylene glycol monomethyl ether, diethylene glycol, dimethyl sulfate, erythritol and xylitol additives.
[0011] The conductive bio-ink with solution processing performance as described above is characterized by a stirring time of 10 min, 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 12 h, 24 h, 36 h, and 72 h. The stirring time is 3.5-4.5 h, and the conductive bio-ink has excellent conductivity after molding ( Figure 3 ).
[0012] The conductive bio-ink with solution processing performance as described above is characterized by the stirring temperature being 25°C, 40°C, 55°C, 70°C, 85°C, and 100°C. The stirring temperature is 20-30°C, and the conductive bio-ink has excellent conductivity after molding ( Figure 4 ).
[0013] (3) Printing or other solution processing methods of the prepared ink on different substrates and heating them to obtain a conductive bio-ink formed material. It is characterized in that the film is dried at different temperatures of 20°C, 40°C, 50°C, 60°C, 80°C, 100°C, and 120°C, and the drying time is 12h, 24h, 36h, and 72h respectively. The cross-linking temperature is 40-60°C, and the cross-linking time is 10-14h. The conductive bio-ink formed material has excellent conductivity ( Figure 5 , Figure 6 ).
[0014] (4) The conductive bio-ink with solution processability was mixed with 5 mg mL -1 The invention is compounded with biological enzymes, characterized in that it contains at least one of biological enzymes such as glucose oxidase, glucose dehydrogenase, galactose oxidase, cholesterol oxidase, amino acid oxidase, alcohol oxidase, lactate oxidase, laccase, catalase and uricase.
[0015] As described above, a method for preparing a material after enzyme-containing conductive biological ink is formed, wherein the substrate is at least one of a platinum electrode, a gold electrode, a silver electrode, an iron electrode, paper, indium tin oxide (ITO), glass, polyethylene terephthalate (PET), polyimide (PI), polypropylene (PP) and the like.
[0016] The present invention has three purposes: first, to provide a conductive bio-ink product having good conductivity, solution processability, biocompatibility, water phase stability, and anti-fouling properties; second, to provide a preparation method that maintains the conductivity and water phase stability of the multifunctional ink by means of the above-mentioned material properties; and third, to provide an efficient solution preparation method suitable for large-scale production of the sensing material.
[0017] The inventive principle of the present invention is as follows:
[0018] The present invention prepares a solution-processable zwitterionic functionalized poly (3,4-ethylenedioxythiophene): polystyrene sulfonate polymer-based ink by oxidative polymerization. The zwitterionic functionalized poly (3,4-ethylenedioxythiophene) combines with the polystyrene sulfonate chain through ionic interaction to form a stable complex. In this composite structure, the polystyrene sulfonate can not only play a role in charge compensation, but also provide water solubility, so that the zwitterionic functionalized poly (3,4-ethylenedioxythiophene) and polystyrene sulfonate have excellent solution processing performance.
[0019] The zwitterion functionalized poly (3,4-ethylenedioxythiophene) in the present invention is electrostatically neutral, which can reduce charge interference, thereby protecting the structure and activity of the enzyme. In addition, the zwitterion functionalized poly (3,4-ethylenedioxythiophene) has superhydrophilicity and can provide a hydrophilic microenvironment, thereby protecting the activity of the enzyme. In addition, by regulating the ratio of the ion functionalized poly (3,4-ethylenedioxythiophene) and polystyrene sulfonate, a milder aqueous solution environment is achieved for the enzyme.
[0020] Through a lot of systematic work, the present invention innovatively discovered that by regulating the cross-linking time and the cross-linking temperature, the conductivity and water phase stability of the material after the conductive bio-ink is formed can be well balanced. The present invention found that increasing the cross-linking temperature and extending the cross-linking time will accelerate the cross-linking speed and shorten the phase migration window. At the same time, increasing the cross-linking temperature and extending the cross-linking time will promote the movement of molecular chains, which is conducive to phase migration. Therefore, the increase in temperature shortens the phase migration time window on the one hand, and accelerates the phase migration on the other hand, resulting in the improvement of the conductivity of zwitterionic functionalized poly 3,4-ethylenedioxythiophene: polystyrene sulfonate and the degree of cross-linking showing an antagonistic trend. Therefore, the present invention balances the cross-linking speed and the phase migration speed by regulating the cross-linking time and the cross-linking temperature, so that the material after the conductive bio-ink is formed has excellent conductivity and water phase stability.
[0021] The material formed by the enzyme-containing conductive bio-ink in the present invention can maintain enzyme activity, has excellent biocompatibility, and has excellent anti-fouling properties. First, by adjusting the process conditions such as the cross-linking temperature and the cross-linking time, the cross-linking curing temperature is relatively mild and does not destroy the enzyme activity. In addition, the hydrophilicity of the zwitterionic functionalized poly 3,4-ethylenedioxythiophene will weaken the interaction between the enzyme and the material, thereby maintaining the conformation of the enzyme. The anions and cations with the same charge in the zwitterionic functionalized poly 3,4-ethylenedioxythiophene unit combine with water through ionic action to form a dense hydration layer, thereby showing excellent anti-nonspecific protein / cell adhesion properties. Therefore, the zwitterionic functionalized poly 3,4-ethylenedioxythiophene: polystyrene sulfonate material prepared in the present invention can effectively maintain the enzyme activity in the enzyme-based sensor, and has excellent anti-fouling properties, which can effectively improve the sensitivity of the sensor and the long-term stability in complex environments.
[0022] Beneficial effects:
[0023] The invention provides a conductive biological ink product with solution processability, wherein the ink has excellent solution processability and biocompatibility.
[0024] The present invention provides a method for preparing conductive bio-ink molding, and the material after the conductive bio-ink molding has good conductivity and water phase stability by regulating the cross-linking temperature and the cross-linking time.
[0025] The material formed by the enzyme-containing conductive biological ink prepared by the invention has excellent biocompatibility and anti-fouling performance.
[0026] The conductive bio-ink product prepared by the present invention has a wide range of applications and is suitable for various sensor fields involving bio-enzymes, and is used for implantable, wearable or other types of sensors, such as glucose sensors, lactate sensors, adrenaline sensors, urea sensors, cholesterol sensors, alcohol sensors, amino acid sensors, hydrogen peroxide sensors, etc. In addition, it can also simplify printing, screen printing, roll-to-roll and other processes, greatly reduce processing costs, have excellent solution processability, and have broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 Figure 2. Antifouling properties of zwitterion-functionalized poly (3,4-ethylenedioxythiophene): polystyrene sulfonate.
[0028] Figure 2 Effect diagram of enzyme activity of zwitterion-functionalized poly (3,4-ethylenedioxythiophene):polystyrene sulfonate.
[0029] Figure 3 Effect of different stirring times on the conductive properties of conductive ink.
[0030] Figure 4 Effect of different stirring temperatures on the conductive properties of conductive ink.
[0031] Figure 5 A graph showing how the conductivity of a conductive bio-ink material changes with cross-linking temperature and time after being formed.
[0032] Figure 6 A graph showing how the aqueous phase stability of a conductive bio-ink material changes with cross-linking temperature and time after molding.
[0033] Figure 7 The present invention preferably shows a relative sensitivity diagram of a glucose sensor (Example 1) prepared from a material formed from an enzyme-containing conductive bio-ink. DETAILED DESCRIPTION
[0034] In order to make the present invention more obvious and easy to understand, a preferred embodiment is described in detail as follows. It should be pointed out that the embodiments described below are intended to facilitate the understanding of the present invention and do not have any limiting effect on it.
[0035] The above scheme is further described below in conjunction with specific implementation examples. The preferred embodiments of the present invention are described in detail as follows:
[0036] Example 1
[0037] In this embodiment, a method for preparing a material after forming an enzyme-containing conductive bio-ink comprises the following steps:
[0038] (1) Weigh 184 mg of 30% HPSS aqueous solution in a 10 mL eggplant bottle, add 1 mL of deionized water, and heat at room temperature at 600 r min. -1 Stir for 20 min, weigh 101.2 mg of EDOT-PC from the glove box and dissolve it in 1 mL of deionized water. -1 Stir for 20 min, pour it into HPSS after it is completely dissolved, and heat it at room temperature at 600 r min -1 Stir for 20 min. Weigh 106.6 mg of sodium persulfate as an oxidant and 0.8 mg of ferric sulfate as a catalyst and heat at room temperature at 600 r min -1 Stir for 20 minutes. After it is completely dissolved, add it into the polymer aqueous solution and keep stirring at 400 r min. -1 The mixture was stirred at 30°C for 3 hours to obtain a blue-black liquid. 1.5 g of cation exchange resin Lewatit Mono plus S108 and 1.5 g of anion exchange resin Lewatit MP 62 were added to the blue-black liquid, stirred for 2 hours, and then filtered to obtain the final product PEDOT-PC:PSS polymer 1, which was stored at 4°C.
[0039] (2) Weigh 1 mL of PEDOT-PC:PSS polymer 1 and add it to 0.5 mL of DMSO and 0.05 mL of wetting agent DBSA, mix them, and stir them at room temperature in the dark for 600 r min. -1 After 4 h of maintenance, 0.08 mL of crosslinker GOPS was added and ultrasonicated for 5 min, and then 5 mg of glucose oxidase was mixed with a vortex oscillator for 1 min to prepare a multifunctional enzyme-containing ink. The prepared ink was spin-coated or drop-coated on a substrate (spin coating 1500 r min -1 The mixture was kept for 45 s) and dried on a hot stage at 50°C for 12 h to obtain a glucose sensor.
[0040] (3) A three-electrode system was used, with a platinum mesh as the counter electrode, Ag / AgCl as the reference electrode, and a glucose sensing electrode as the working electrode. The prepared glucose sensor was stored in 1 mg mL -1 The samples were stored in bovine serum albumin (BSA) for 2 weeks to simulate a complex usage environment and stored at 25°C. The current response to 200 μM glucose was tested and then the relative sensitivity was calculated. The relative sensitivity of PEDOT:PSS was 5.1% and that of our sensing material was 75.3%.
[0041] Example 2
[0042] This embodiment is basically the same as Embodiment 1, except that:
[0043] In this embodiment, a method for preparing a material formed from enzyme-containing conductive bio-ink comprises the following steps:
[0044] (1) Weigh 184 mg of 30% HPSS aqueous solution in a 10 mL eggplant bottle, add 1 mL of deionized water, and heat at room temperature at 600 r min. -1 Stir for 20 min, weigh 101.2 mg of EDOT-CB from the glove box and dissolve it in 1 mL of deionized water. -1 Stir for 20 min, pour it into HPSS after it is completely dissolved, and heat it at room temperature at 600 r min -1 Stir for 20 min. Weigh 106.6 mg of sodium persulfate as an oxidant and 0.8 mg of ferric sulfate as a catalyst and heat at room temperature at 600 r min -1 Stir for 20 minutes. After it is completely dissolved, add it into the polymer aqueous solution and keep stirring at 400 r min. -1 The mixture was stirred at 30°C for 3 hours to obtain a blue-black liquid. 1.5 g of cation exchange resin Lewatit Mono plus S108 and 1.5 g of anion exchange resin Lewatit MP 62 were added to the blue-black liquid, stirred for 2 hours, and then filtered to obtain the final product PEDOT-CB:PSS polymer 2, which was stored at 4°C.
[0045] (2) Weigh 1 mL of PEDOT-CB:PSS polymer 2, add 0.5 mL of DMSO and 0.05 mL of wetting agent DBSA, mix, and stir at room temperature in the dark for 600 r min. -1 After 4 h of maintenance, 0.08 mL of crosslinker GOPS was added and ultrasonicated for 5 min, and then 5 mg of glucose oxidase was mixed with a vortex oscillator for 1 min to prepare a multifunctional enzyme-containing ink. The prepared ink was spin-coated or drop-coated on a substrate (spin coating 1500 r min -1 The mixture was kept for 45 s) and dried on a hot stage at 50°C for 12 h to obtain a glucose sensor.
[0046] (3) A three-electrode system was used, with a platinum mesh as the counter electrode, Ag / AgCl as the reference electrode, and a glucose sensing electrode as the working electrode. The prepared glucose sensor was stored in 1 mg mL -1 The samples were stored in bovine serum albumin (BSA) for 2 weeks to simulate a complex usage environment and stored at 25°C. The current response to 200 μM glucose was tested and then the relative sensitivity was calculated. The relative sensitivity of PEDOT:PSS was 5.1% and that of our sensing material was 52.9%.
[0047] Example 3
[0048] This embodiment is basically the same as the above embodiment, with the following features:
[0049] In this embodiment, a method for preparing a material formed from enzyme-containing conductive bio-ink comprises the following steps:
[0050] (1) Weigh 184 mg of 30% HPSS aqueous solution in a 10 mL eggplant bottle, add 1 mL of deionized water, and heat at room temperature at 600 r min. -1 Stir for 20 min, weigh 101.2 mg of EDOT-SB from the glove box and dissolve it in 1 mL of deionized water. -1 Stir for 20 min, pour it into HPSS after it is completely dissolved, and heat it at room temperature at 600 r min -1 Stir for 20 min. Weigh 106.6 mg of sodium persulfate as an oxidant and 0.8 mg of ferric sulfate as a catalyst and heat at room temperature at 600 r min -1 Stir for 20 minutes. After it is completely dissolved, add it into the polymer aqueous solution and keep stirring at 400 r min. -1 The mixture was stirred at 30°C for 3 hours to obtain a blue-black liquid. 1.5 g of cation exchange resin Lewatit Mono plus S108 and 1.5 g of anion exchange resin Lewatit MP 62 were added to the blue-black liquid, stirred for 2 hours, and then filtered to obtain the final product PEDOT-SB:PSS polymer 3, which was stored at 4°C.
[0051] (2) Weigh 1 mL of PEDOT-SB:PSS polymer 3 and add it to 0.5 mL of DMSO and 0.05 mL of wetting agent DBSA, mix them, and stir them at room temperature in the dark for 600 min. -1 After 4 h of maintenance, 0.08 mL of crosslinker GOPS was added and ultrasonicated for 5 min, and then 5 mg of glucose oxidase was mixed with a vortex oscillator for 1 min to prepare a multifunctional enzyme-containing ink. The prepared ink was spin-coated or drop-coated on a substrate (spin coating 1500 r min -1 The mixture was kept for 45 s) and dried on a hot stage at 50°C for 12 h to obtain a glucose sensor.
[0052] (3) A three-electrode system was used, with a platinum mesh as the counter electrode, Ag / AgCl as the reference electrode, and a glucose sensing electrode as the working electrode. The prepared glucose sensor was stored in 1 mg mL -1The samples were stored in bovine serum albumin (BSA) for 2 weeks to simulate a complex usage environment and stored at 25°C. The current response to 200 μM glucose was tested and then the relative sensitivity was calculated. The relative sensitivity of PEDOT:PSS was 5.1% and that of our sensing material was 55.4%.
[0053] Example 4
[0054] This embodiment is basically the same as the above embodiment, with the following features:
[0055] In this embodiment, a method for preparing a material formed from enzyme-containing conductive bio-ink comprises the following steps:
[0056] (1) Weigh 368 mg of 30% HPSS aqueous solution in a 10 mL eggplant bottle, add 1 mL of deionized water, and heat at room temperature at 600 r min. -1 Stir for 20 min, weigh 101.2 mg of EDOT-PC from the glove box and dissolve it in 1 mL of deionized water. -1 Stir for 20 min, pour it into HPSS after it is completely dissolved, and heat it at room temperature at 600 r min -1 Stir for 20 min. Weigh 106.6 mg of sodium persulfate as an oxidant and 0.8 mg of ferric sulfate as a catalyst and heat at room temperature at 600 r min -1 Stir for 20 minutes. After it is completely dissolved, add it into the polymer aqueous solution and keep stirring at 400 r min. -1 The mixture was stirred at 30°C for 3 hours to obtain a blue-black liquid. 1.5 g of cation exchange resin Lewatit Mono plus S108 and 1.5 g of anion exchange resin Lewatit MP 62 were added to the blue-black liquid, stirred for 2 hours, and then filtered to obtain the final product PEDOT-PC:PSS polymer 4, which was stored at 4°C.
[0057] (2) Weigh 1 mL of PEDOT-PC:PSS polymer 4 and add it to 0.5 mL of DMSO and 0.05 mL of wetting agent DBSA, mix them, and stir them at room temperature in the dark for 600 r min. -1 After 4 h of maintenance, 0.08 mL of crosslinker GOPS was added and ultrasonicated for 5 min, and then 5 mg of glucose oxidase was mixed with a vortex oscillator for 1 min to prepare a multifunctional enzyme-containing ink. The prepared ink was spin-coated or drop-coated on a substrate (spin coating 1500 r min -1 The mixture was kept for 45 s) and dried on a hot stage at 50°C for 12 h to obtain a glucose sensor.
[0058] (3) A three-electrode system was used, with a platinum mesh as the counter electrode, Ag / AgCl as the reference electrode, and a glucose sensing electrode as the working electrode. The prepared glucose sensor was stored in 1 mg mL -1 The samples were stored in bovine serum albumin (BSA) for 2 weeks to simulate a complex usage environment and stored at 25°C. The current response to 200 μM glucose was tested and then the relative sensitivity was calculated. The relative sensitivity of PEDOT:PSS was 5.1% and that of our sensing material was 57.1%.
[0059] Example 5
[0060] This embodiment is basically the same as the above embodiment, with the following features:
[0061] In this embodiment, a method for preparing a material formed from enzyme-containing conductive bio-ink comprises the following steps:
[0062] (1) Weigh 552 mg of 30% HPSS aqueous solution in a 10 mL eggplant bottle, add 1 mL of deionized water, and heat at room temperature at 600 r min. -1 Stir for 20 min, weigh 101.2 mg of EDOT-PC from the glove box and dissolve it in 1 mL of deionized water. -1 Stir for 20 min, pour it into HPSS after it is completely dissolved, and heat it at room temperature at 600 r min -1 Stir for 20 min. Weigh 106.6 mg of sodium persulfate as an oxidant and 0.8 mg of ferric sulfate as a catalyst and heat at room temperature at 600 r min -1 Stir for 20 minutes. After it is completely dissolved, add it into the polymer aqueous solution and keep stirring at 400 r min. -1 The mixture was stirred at 30°C for 3 hours to obtain a blue-black liquid. 1.5 g of cation exchange resin Lewatit Mono plus S108 and 1.5 g of anion exchange resin Lewatit MP 62 were added to the blue-black liquid, stirred for 2 hours, and then filtered to obtain the final product PEDOT-PC:PSS polymer 5, which was stored at 4°C.
[0063] (2) Weigh 1 mL of PEDOT-PC:PSS polymer 5, add it to 0.5 mL of DMSO and 0.05 mL of wetting agent DBSA, mix them, and stir them at room temperature in the dark for 600 r min. -1 After 4 h of maintenance, 0.08 mL of crosslinker GOPS was added and ultrasonicated for 5 min, and then 5 mg of glucose oxidase was mixed with a vortex oscillator for 1 min to prepare a multifunctional enzyme-containing ink. The prepared ink was spin-coated or drop-coated on a substrate (spin coating 1500 r min -1The mixture was kept for 45 s) and dried on a hot stage at 50°C for 12 h to obtain a glucose sensor.
[0064] (3) A three-electrode system was used, with a platinum mesh as the counter electrode, Ag / AgCl as the reference electrode, and a glucose sensing electrode as the working electrode. The prepared glucose sensor was stored in 1 mg mL -1 After 2 weeks in bovine serum albumin (BSA), the complex use environment was simulated and the storage temperature was 25°C. The current response to 200μM glucose was tested and then the relative sensitivity was calculated. The relative sensitivity of PEDOT:PSS was 5.1% and that of our sensing material was 33.3%.
[0065] Example 6
[0066] This embodiment is basically the same as the above embodiment, with the following features:
[0067] In this embodiment, a method for preparing a material formed from enzyme-containing conductive bio-ink comprises the following steps:
[0068] (1) Weigh 184 mg of 30% HPSS aqueous solution in a 10 mL eggplant bottle, add 1 mL of deionized water, and heat at room temperature at 600 r min. -1 Stir for 20 min, weigh 101.2 mg of EDOT-PC from the glove box and dissolve it in 1 mL of deionized water. -1 Stir for 20 min, pour it into HPSS after it is completely dissolved, and heat it at room temperature at 600 r min -1 Stir for 20 min. Weigh 106.6 mg of sodium persulfate as an oxidant and 0.8 mg of ferric sulfate as a catalyst and heat at room temperature at 600 r min -1 Stir for 20 minutes. After it is completely dissolved, add it into the polymer aqueous solution and keep stirring at 400 r min. -1 The mixture was stirred at 30°C for 3 hours to obtain a blue-black liquid. 1.5 g of cation exchange resin Lewatit Mono plus S108 and 1.5 g of anion exchange resin Lewatit MP 62 were added to the blue-black liquid, stirred for 2 hours, and then filtered to obtain the final product PEDOT-PC:PSS polymer 6, which was stored at 4°C.
[0069] (2) Weigh 1 mL of PEDOT-PC:PSS polymer 6 and add it to 0.5 mL of DMSO and 0.05 mL of wetting agent DBSA, mix them, and stir them at room temperature in the dark for 600 min. -1After 4 h of maintenance, 0.08 mL of crosslinker GOPS was added and ultrasonicated for 5 min, and then 5 mg of lactate oxidase was mixed with a vortex oscillator for 1 min to prepare a multifunctional enzyme-containing ink. The prepared ink was spin-coated or drop-coated on a substrate (spin coating 1500 r min -1 The resulting mixture was kept for 45 seconds and dried on a hot stage at 50°C for 12 hours to obtain a lactic acid sensor.
[0070] (3) A three-electrode system was used, with a platinum mesh as the counter electrode, Ag / AgCl as the reference electrode, and a lactate sensing electrode as the working electrode. The prepared lactate sensor was stored in 1 mg mL -1 The samples were stored in bovine serum albumin (BSA) for 2 weeks to simulate a complex usage environment and stored at 25°C. The current response to 200 μM lactic acid was tested and then the relative sensitivity was calculated. The relative sensitivity of PEDOT:PSS was 5.1% and that of our sensing material was 73.3%.
[0071] Example 7
[0072] This embodiment is basically the same as the above embodiment, with the following features:
[0073] In this embodiment, a method for preparing a material formed from enzyme-containing conductive bio-ink comprises the following steps:
[0074] (1) Weigh 184 mg of 30% HPSS aqueous solution in a 10 mL eggplant bottle, add 1 mL of deionized water, and heat at room temperature at 600 r min. -1 Stir for 20 min, weigh 101.2 mg of EDOT-PC from the glove box and dissolve it in 1 mL of deionized water. -1 Stir for 20 min, pour it into HPSS after it is completely dissolved, and heat it at room temperature at 600 r min -1 Stir for 20 min. Weigh 106.6 mg of sodium persulfate as an oxidant and 0.8 mg of ferric sulfate as a catalyst and heat at room temperature at 600 r min -1 Stir for 20 minutes. After it is completely dissolved, add it into the polymer aqueous solution and keep stirring at 400 r min. -1 The mixture was stirred at 30°C for 3 hours to obtain a blue-black liquid. 1.5 g of cation exchange resin Lewatit Mono plus S108 and 1.5 g of anion exchange resin Lewatit MP 62 were added to the blue-black liquid, stirred for 2 hours, and then filtered to obtain the final product PEDOT-PC:PSS polymer 7, which was stored at 4°C.
[0075] (2) Weigh 1 mL of PEDOT-PC:PSS polymer 7 and add it to 0.5 mL of DMSO and 0.05 mL of wetting agent DBSA, mix them, and stir them at room temperature in the dark for 600 r min. -1 After 4 h of maintenance, 0.08 mL of crosslinking agent GOPS was added and ultrasonicated for 5 min, and then 5 mg of laccase was mixed by vortex oscillator for 1 min to prepare a multifunctional enzyme-containing ink. The prepared ink was spin-coated or drop-coated on the substrate (spin coating 1500 r min -1 The resulting solution was kept for 45 seconds and dried on a hot stage at 50°C for 12 hours to obtain a catecholamine sensor.
[0076] (3) A three-electrode system was used, with a platinum mesh as the counter electrode, Ag / AgCl as the reference electrode, and a catecholamine sensing electrode as the working electrode. The prepared catecholamine sensor was stored in 1 mg mL -1 The samples were stored in bovine serum albumin (BSA) for 2 weeks to simulate a complex usage environment and stored at 25°C. The current response to 200 μM catecholamine was tested and then the relative sensitivity was calculated. The relative sensitivity of PEDOT:PSS was 3.2% and that of our sensing material was 71.5%.
[0077] Example 8
[0078] This embodiment is basically the same as the above embodiment, with the following features:
[0079] In this embodiment, a method for preparing a material formed from enzyme-containing conductive bio-ink comprises the following steps:
[0080] (1) Weigh 184 mg of 30% HPSS aqueous solution in a 10 mL eggplant bottle, add 1 mL of deionized water, and heat at room temperature at 600 r min. -1 Stir for 20 min, weigh 101.2 mg of EDOT-PC from the glove box and dissolve it in 1 mL of deionized water. -1 Stir for 20 min, pour it into HPSS after it is completely dissolved, and heat it at room temperature at 600 r min -1 Stir for 20 min. Weigh 106.6 mg of sodium persulfate as an oxidant and 0.8 mg of ferric sulfate as a catalyst and heat at room temperature at 600 r min -1 Stir for 20 minutes. After it is completely dissolved, add it into the polymer aqueous solution and keep stirring at 400 r min. -1The mixture was stirred at 30°C for 3 hours to obtain a blue-black liquid. 1.5 g of cation exchange resin Lewatit Mono plus S108 and 1.5 g of anion exchange resin Lewatit MP 62 were added to the blue-black liquid, stirred for 2 hours, and then filtered to obtain the final product PEDOT-PC:PSS polymer 8, which was stored at 4°C.
[0081] (2) Weigh 1 mL of PEDOT-PC:PSS polymer 8 and add it to 0.5 mL of DMSO and 0.05 mL of wetting agent DBSA, mix them, and stir them at room temperature in the dark for 600 min. -1 After 4 h of maintenance, 0.08 mL of crosslinking agent GOPS was added and ultrasonicated for 5 min, and then 5 mg of uricase was mixed by vortex oscillator for 1 min to prepare a multifunctional enzyme-containing ink. The prepared ink was spin-coated or drop-coated on the substrate (spin coating 1500 r min -1 The uric acid sensor was prepared by drying on a hot stage at 50°C for 12 h.
[0082] (3) A three-electrode system was used, with a platinum mesh as the counter electrode, Ag / AgCl as the reference electrode, and a uric acid sensing electrode as the working electrode. The prepared uric acid sensor was stored in 1 mg mL -1 The samples were stored in bovine serum albumin (BSA) for 2 weeks to simulate a complex usage environment and stored at 25°C. The current response to 200 μM uric acid was tested and then the relative sensitivity was calculated. The relative sensitivity of PEDOT:PSS was 7.9% and that of our sensing material was 72.8%.
[0083] Example 9
[0084] This embodiment is basically the same as the above embodiment, with the following features:
[0085] In this embodiment, a method for preparing a material formed from enzyme-containing conductive bio-ink comprises the following steps:
[0086] (1) Weigh 184 mg of 30% HPSS aqueous solution in a 10 mL eggplant bottle, add 1 mL of deionized water, and heat at room temperature at 600 r min. -1 Stir for 20 min, weigh 101.2 mg of EDOT-PC from the glove box and dissolve it in 1 mL of deionized water. -1 Stir for 20 min, pour it into HPSS after it is completely dissolved, and heat it at room temperature at 600 r min -1 Stir for 20 min. Weigh 106.6 mg of sodium persulfate as an oxidant and 0.8 mg of ferric sulfate as a catalyst and heat at room temperature at 600 r min -1Stir for 20 minutes. After it is completely dissolved, add it into the polymer aqueous solution and keep stirring at 400 r min. -1 The mixture was stirred at 30°C for 3 hours to obtain a blue-black liquid. 1.5 g of cation exchange resin Lewatit Mono plus S108 and 1.5 g of anion exchange resin Lewatit MP 62 were added to the blue-black liquid, stirred for 2 hours, and then filtered to obtain the final product PEDOT-PC:PSS polymer 9, which was stored at 4°C.
[0087] (2) Weigh 1 mL of PEDOT-PC:PSS polymer 9 and add it to 0.5 mL of DMSO and 0.05 mL of wetting agent DBSA, mix them, and stir them at room temperature in the dark for 600 min. -1 After 4 h of maintenance, 0.08 mL of crosslinker GOPS was added and ultrasonicated for 5 min, and then 5 mg of cholesterol oxidase was mixed with a vortex oscillator for 1 min to prepare a multifunctional enzyme-containing ink. The prepared ink was spin-coated or drop-coated on a substrate (spin coating 1500 r min -1 The resulting mixture was kept for 45 seconds and dried on a hot stage at 50°C for 12 hours to obtain a cholesterol sensor.
[0088] (3) A three-electrode system was used, with a platinum mesh as the counter electrode, Ag / AgCl as the reference electrode, and a cholesterol sensing electrode as the working electrode. The prepared cholesterol sensor was stored in 1 mg mL -1 The samples were stored in bovine serum albumin (BSA) for 2 weeks to simulate a complex usage environment and stored at 25°C. The current response to 200 μM cholesterol was tested and then the relative sensitivity was calculated. The relative sensitivity of PEDOT:PSS was 5.8% and that of our sensing material was 71.9%.
[0089] Example 10
[0090] This embodiment is basically the same as the above embodiment, with the following features:
[0091] In this embodiment, a method for preparing a material formed from enzyme-containing conductive bio-ink comprises the following steps:
[0092] (1) Weigh 184 mg of 30% HPSS aqueous solution in a 10 mL eggplant bottle, add 1 mL of deionized water, and heat at room temperature at 600 r min. -1 Stir for 20 min, weigh 101.2 mg of EDOT-PC from the glove box and dissolve it in 1 mL of deionized water. -1 Stir for 20 min, pour it into HPSS after it is completely dissolved, and heat it at room temperature at 600 r min -1Stir for 20 min. Weigh 106.6 mg of sodium persulfate as an oxidant and 0.8 mg of ferric sulfate as a catalyst and heat at room temperature at 600 r min -1 Stir for 20 minutes. After it is completely dissolved, add it into the polymer aqueous solution and keep stirring at 400 r min. -1 The mixture was stirred at 30°C for 3 hours to obtain a blue-black liquid. 1.5 g of cation exchange resin Lewatit Mono plus S108 and 1.5 g of anion exchange resin Lewatit MP 62 were added to the blue-black liquid, stirred for 2 hours, and then filtered to obtain the final product PEDOT-PC:PSS polymer 10, which was stored at 4°C.
[0093] (2) Weigh 1 mL of PEDOT-PC:PSS polymer 10, add it to 0.5 mL of ethylene glycol and 0.05 mL of wetting agent DBSA, mix them, and stir them at room temperature in the dark for 600 r min. -1 After 4 h of maintenance, 0.08 mL of crosslinker GOPS was added and ultrasonicated for 5 min, and then 5 mg of glucose oxidase was mixed with a vortex oscillator for 1 min to prepare a multifunctional enzyme-containing ink. The prepared ink was spin-coated or drop-coated on a substrate (spin coating 1500 r min -1 The mixture was kept for 45 s) and dried on a hot stage at 50°C for 12 h to obtain a glucose sensor.
[0094] (3) A three-electrode system was used, with a platinum mesh as the counter electrode, Ag / AgCl as the reference electrode, and a glucose sensing electrode as the working electrode. The prepared glucose sensor was stored in 1 mg mL -1 The samples were stored in bovine serum albumin (BSA) for 2 weeks to simulate a complex usage environment and stored at 25°C. The current response to 200 μM glucose was tested and then the relative sensitivity was calculated. The relative sensitivity of PEDOT:PSS was 4.3% and that of our sensing material was 69.3%.
[0095] Embodiment 11
[0096] This embodiment is basically the same as the above embodiment, with the following features:
[0097] In this embodiment, a method for preparing a material formed from enzyme-containing conductive bio-ink comprises the following steps:
[0098] (1) Weigh 184 mg of 30% HPSS aqueous solution in a 10 mL eggplant bottle, add 1 mL of deionized water, and heat at room temperature at 600 r min. -1 Stir for 20 min, weigh 101.2 mg of EDOT-PC from the glove box and dissolve it in 1 mL of deionized water.-1 Stir for 20 min, pour it into HPSS after it is completely dissolved, and heat it at room temperature at 600 r min -1 Stir for 20 min. Weigh 106.6 mg of sodium persulfate as an oxidant and 0.8 mg of ferric sulfate as a catalyst and heat at room temperature at 600 r min -1 Stir for 20 minutes. After it is completely dissolved, add it into the polymer aqueous solution and keep stirring at 400 r min. -1 The mixture was stirred at 30°C for 3 hours to obtain a blue-black liquid. 1.5 g of cation exchange resin Lewatit Mono plus S108 and 1.5 g of anion exchange resin Lewatit MP 62 were added to the blue-black liquid, stirred for 2 hours, and then filtered to obtain the final product PEDOT-PC:PSS polymer 11, which was stored at 4°C.
[0099] (2) Weigh 1 mL of PEDOT-PC:PSS polymer 11 and add it to 0.5 mL of dimethylformamide and 0.05 mL of wetting agent DBSA, mix them, and stir them at room temperature in the dark for 600 r min. -1 After 4 h of maintenance, 0.08 mL of crosslinker GOPS was added and ultrasonicated for 5 min, and then 5 mg of glucose oxidase was mixed with a vortex oscillator for 1 min to prepare a multifunctional enzyme-containing ink. The prepared ink was spin-coated or drop-coated on a substrate (spin coating 1500 r min -1 The mixture was kept for 45 s) and dried on a hot stage at 50°C for 12 h to obtain a glucose sensor.
[0100] (3) A three-electrode system was used. The counter electrode was a platinum mesh, the reference electrode was Ag / AgCl, and the working electrode was a glucose sensor electrode. The prepared glucose sensor was stored in 1 mg mL -1 The samples were stored in bovine serum albumin (BSA) for 2 weeks to simulate a complex usage environment and stored at 25°C. The current response to 200 μM glucose was tested and then the relative sensitivity was calculated. The relative sensitivity of PEDOT:PSS was 3.2% and that of our sensing material was 68.9%.
[0101] Example 12
[0102] This embodiment is basically the same as the above embodiment, with the following features:
[0103] In this embodiment, a method for preparing a material formed from enzyme-containing conductive bio-ink comprises the following steps:
[0104] (1) Weigh 184 mg of 30% HPSS aqueous solution in a 10 mL eggplant bottle, add 1 mL of deionized water, and heat at room temperature at 600 r min. -1Stir for 20 min, weigh 101.2 mg of EDOT-PC from the glove box and dissolve it in 1 mL of deionized water. -1 Stir for 20 min, pour it into HPSS after it is completely dissolved, and heat it at room temperature at 600 r min -1 Stir for 20 min. Weigh 106.6 mg of sodium persulfate as an oxidant and 0.8 mg of ferric sulfate as a catalyst and heat at room temperature at 600 r min -1 Stir for 20 minutes. After it is completely dissolved, add it into the polymer aqueous solution and keep stirring at 400 r min. -1 The mixture was stirred at 30°C for 3 hours to obtain a blue-black liquid. 1.5 g of cation exchange resin Lewatit Mono plus S108 and 1.5 g of anion exchange resin Lewatit MP 62 were added to the blue-black liquid, stirred for 2 hours, and then filtered to obtain the final product PEDOT-PC:PSS polymer 12, which was stored at 4°C.
[0105] (2) Weigh 1 mL of PEDOT-PC:PSS polymer 12, add it to 0.5 mL of tetrahydrofuran and 0.05 mL of wetting agent DBSA, mix them, and stir them at room temperature in the dark for 600 r min. -1 After 4 h of maintenance, 0.08 mL of crosslinker GOPS was added and ultrasonicated for 5 min, and then 5 mg of glucose oxidase was mixed with a vortex oscillator for 1 min to prepare a multifunctional enzyme-containing ink. The prepared ink was spin-coated or drop-coated on a substrate (spin coating 1500 r min -1 The mixture was kept for 45 s) and dried on a hot stage at 50°C for 12 h to obtain a glucose sensor.
[0106] (3) A three-electrode system was used, with a platinum mesh as the counter electrode, Ag / AgCl as the reference electrode, and a glucose sensing electrode as the working electrode. The prepared glucose sensor was stored in 1 mg mL -1 The samples were stored in bovine serum albumin (BSA) for 2 weeks to simulate a complex usage environment and stored at 25°C. The current response to 200 μM glucose was tested and then the relative sensitivity was calculated. The relative sensitivity of PEDOT:PSS was 6.4% and that of our sensing material was 59.4%.
[0107] Embodiment 13
[0108] This embodiment is basically the same as the above embodiment, with the following features:
[0109] In this embodiment, a method for preparing a material formed from enzyme-containing conductive bio-ink comprises the following steps:
[0110] (1) Weigh 184 mg of 30% HPSS aqueous solution in a 10 mL eggplant bottle, add 1 mL of deionized water, and heat at room temperature at 600 r min. -1 Stir for 20 min, weigh 101.2 mg of EDOT-PC from the glove box and dissolve it in 1 mL of deionized water. -1 Stir for 20 min, pour it into HPSS after it is completely dissolved, and heat it at room temperature at 600 r min -1 Stir for 20 min. Weigh 106.6 mg of sodium persulfate as an oxidant and 0.8 mg of ferric sulfate as a catalyst and heat at room temperature at 600 r min -1 Stir for 20 minutes, and after it is completely dissolved, add the aqueous solution of catalyst and oxidant, and keep stirring for 400 r min. -1 The mixture was stirred at 30°C for 3 hours to obtain a blue-black liquid. 1.5 g of cation exchange resin Lewatit Mono plus S108 and 1.5 g of anion exchange resin Lewatit MP 62 were added to the blue-black liquid, stirred for 2 hours, and then filtered to obtain the final product PEDOT-PC:PSS polymer 13, which was stored at 4°C.
[0111] (2) Weigh 1 mL of PEDOT-PC:PSS polymer 13, add it to 0.5 mL of propylene glycol and 0.05 mL of wetting agent DBSA, mix them, and stir them at room temperature in the dark for 600 r min. -1 After 4 h of maintenance, 0.08 mL of crosslinking agent GOPS was added and ultrasonicated for 5 min, and then 5 mg of glucose oxidase was mixed with a vortex oscillator for 1 min to prepare a multifunctional enzyme-containing ink. The prepared ink was spin-coated or drop-coated on a substrate (spin coating 1500 r min -1 Keep for 45 seconds). Dry at 50°C on a hot stage for 12 hours to obtain a glucose sensor.
[0112] (3) A three-electrode system was used. The counter electrode was a platinum mesh, the reference electrode was Ag / AgCl, and the working electrode was a glucose sensor electrode. The prepared glucose sensor was stored in 1 mg mL -1 After 2 weeks in bovine serum albumin (BSA), the complex use environment was simulated and the storage temperature was 25°C. The current response to 200μM glucose was tested and then the relative sensitivity was calculated. The relative sensitivity of PEDOT:PSS was 3.1% and the relative sensitivity of our sensing material was 61.6%.
[0113] Embodiment 14
[0114] This embodiment is basically the same as the above embodiment, with the following features:
[0115] In this embodiment, a method for preparing a material formed from enzyme-containing conductive bio-ink comprises the following steps:
[0116] (1) Weigh 184 mg of 30% HPSS aqueous solution in a 10 mL eggplant bottle, add 1 mL of deionized water, and heat at room temperature at 600 r min. -1 Stir for 20 min, weigh 101.2 mg of EDOT-PC from the glove box and dissolve it in 1 mL of deionized water. -1 Stir for 20 min, pour it into HPSS after it is completely dissolved, and heat it at room temperature at 600 r min -1 Stir for 20 min. Weigh 106.6 mg of sodium persulfate as an oxidant and 0.8 mg of ferric sulfate as a catalyst and heat at room temperature at 600 r min -1 Stir for 20 minutes. After it is completely dissolved, add it into the polymer aqueous solution and keep stirring at 400 r min. -1 The mixture was stirred at 30°C for 3 hours to obtain a blue-black liquid. 1.5 g of cation exchange resin Lewatit Mono plus S108 and 1.5 g of anion exchange resin Lewatit MP 62 were added to the blue-black liquid, stirred for 2 hours, and then filtered to obtain the final product PEDOT-PC:PSS polymer 14, which was stored at 4°C.
[0117] (2) Weigh 1 mL of PEDOT-PC:PSS polymer 14, add it to 0.5 mL of sorbitol and 0.05 mL of wetting agent DBSA, mix them, and stir them at room temperature in the dark for 600 r min. -1 After 4 h of maintenance, 0.08 mL of crosslinker GOPS was added and ultrasonicated for 5 min, and then 5 mg of glucose oxidase was mixed with a vortex oscillator for 1 min to prepare a multifunctional enzyme-containing ink. The prepared ink was spin-coated or drop-coated on a substrate (spin coating 1500 r min -1 The mixture was kept for 45 s) and dried on a hot stage at 50°C for 12 h to obtain a glucose sensor.
[0118] (3) A three-electrode system was used, with a platinum mesh as the counter electrode, Ag / AgCl as the reference electrode, and a glucose sensing electrode as the working electrode. The prepared glucose sensor was stored in 1 mg mL -1 The samples were stored in bovine serum albumin (BSA) for 2 weeks to simulate a complex usage environment and stored at 25°C. The current response to 200 μM glucose was tested and then the relative sensitivity was calculated. The relative sensitivity of PEDOT:PSS was 3.5% and that of our sensing material was 56.9%.
[0119] Embodiment 15
[0120] This embodiment is basically the same as the above embodiment, with the following features:
[0121] In this embodiment, a method for preparing a material formed from enzyme-containing conductive bio-ink comprises the following steps:
[0122] (1) Weigh 184 mg of 30% HPSS aqueous solution in a 10 mL eggplant bottle, add 1 mL of deionized water, and heat at room temperature at 600 r min. -1 Stir for 20 min, weigh 101.2 mg of EDOT-PC from the glove box and dissolve it in 1 mL of deionized water. -1 Stir for 20 min, pour it into HPSS after it is completely dissolved, and heat it at room temperature at 600 r min -1 Stir for 20 min. Weigh 106.6 mg of sodium persulfate as an oxidant and 0.8 mg of ferric sulfate as a catalyst and heat at room temperature at 600 r min -1 Stir for 20 minutes. After it is completely dissolved, add it into the polymer aqueous solution and keep stirring at 400 r min. -1 The mixture was stirred at 30°C for 3 hours to obtain a blue-black liquid. 1.5 g of cation exchange resin Lewatit Mono plus S108 and 1.5 g of anion exchange resin Lewatit MP 62 were added to the blue-black liquid, stirred for 2 hours, and then filtered to obtain the final product PEDOT-PC:PSS polymer 15, which was stored at 4°C.
[0123] (2) Weigh 1 mL of PEDOT-PC:PSS polymer 15, add it to 0.5 mL of ethylene glycol monomethyl ether and 0.05 mL of wetting agent DBSA, mix them, and stir them at room temperature in the dark for 600 r min. -1 After 4 h of maintenance, 0.08 mL of crosslinker GOPS was added and ultrasonicated for 5 min, and then 5 mg of glucose oxidase was mixed with a vortex oscillator for 1 min to prepare a multifunctional enzyme-containing ink. The prepared ink was spin-coated or drop-coated on a substrate (spin coating 1500 r min -1 The mixture was kept for 45 s) and dried on a hot stage at 50°C for 12 h to obtain a glucose sensor.
[0124] (3) A three-electrode system was used, with a platinum mesh as the counter electrode, Ag / AgCl as the reference electrode, and a glucose sensing electrode as the working electrode. The prepared glucose sensor was stored in 1 mg mL -1The samples were stored in bovine serum albumin (BSA) for 2 weeks to simulate a complex usage environment and stored at 25°C. The current response to 200 μM glucose was tested and then the relative sensitivity was calculated. The relative sensitivity of PEDOT:PSS was 2.7% and that of our sensing material was 57.1%.
[0125] Example 16
[0126] This embodiment is basically the same as the above embodiment, with the following features:
[0127] In this embodiment, a method for preparing a material formed from enzyme-containing conductive bio-ink comprises the following steps:
[0128] (1) Weigh 184 mg of 30% HPSS aqueous solution in a 10 mL eggplant bottle, add 1 mL of deionized water, and heat at room temperature at 600 r min. -1 Stir for 20 min, weigh 101.2 mg of EDOT-PC from the glove box and dissolve it in 1 mL of deionized water. -1 Stir for 20 min, pour it into HPSS after it is completely dissolved, and heat it at room temperature at 600 r min -1 Stir for 20 min. Weigh 106.6 mg of sodium persulfate as an oxidant and 0.8 mg of ferric sulfate as a catalyst and heat at room temperature at 600 r min -1 Stir for 20 minutes. After it is completely dissolved, add it into the polymer aqueous solution and keep stirring at 400 r min. -1 The mixture was stirred at 30°C for 3 hours to obtain a blue-black liquid. 1.5 g of cation exchange resin Lewatit Mono plus S108 and 1.5 g of anion exchange resin Lewatit MP 62 were added to the blue-black liquid, stirred for 2 hours, and then filtered to obtain the final product PEDOT-PC:PSS polymer 16, which was stored at 4°C.
[0129] (2) Weigh 1 mL of PEDOT-PC:PSS polymer 16, add it to 0.5 mL of diethylene glycol and 0.05 mL of wetting agent DBSA, mix them, and stir them at room temperature in the dark for 600 r min. -1 After 4 h of maintenance, 0.08 mL of crosslinker GOPS was added and ultrasonicated for 5 min, and then 5 mg of glucose oxidase was mixed with a vortex oscillator for 1 min to prepare a multifunctional enzyme-containing ink. The prepared ink was spin-coated or drop-coated on a substrate (spin coating 1500 r min -1 The mixture was kept for 45 s) and dried on a hot stage at 50°C for 12 h to obtain a glucose sensor.
[0130] (3) A three-electrode system was used, with a platinum mesh as the counter electrode, Ag / AgCl as the reference electrode, and a glucose sensing electrode as the working electrode. The prepared glucose sensor was stored in 1 mg mL -1 The samples were stored in bovine serum albumin (BSA) for 2 weeks to simulate a complex usage environment and stored at 25°C. The current response to 200 μM glucose was tested and then the relative sensitivity was calculated. The relative sensitivity of PEDOT:PSS was 2.9% and that of our sensing material was 59.3%.
[0131] Embodiment 17
[0132] This embodiment is basically the same as the above embodiment, with the following features:
[0133] In this embodiment, a method for preparing a material formed from enzyme-containing conductive bio-ink comprises the following steps:
[0134] (1) Weigh 184 mg of 30% HPSS aqueous solution in a 10 mL eggplant bottle, add 1 mL of deionized water, and heat at room temperature at 600 r min. -1 Stir for 20 min, weigh 101.2 mg of EDOT-PC from the glove box and dissolve it in 1 mL of deionized water. -1 Stir for 20 min, pour it into HPSS after it is completely dissolved, and heat it at room temperature at 600 r min -1 Stir for 20 min. Weigh 106.6 mg of sodium persulfate as an oxidant and 0.8 mg of ferric sulfate as a catalyst and heat at room temperature at 600 r min -1 Stir for 20 minutes. After it is completely dissolved, add it into the polymer aqueous solution and keep stirring at 400 r min. -1 The mixture was stirred at 30°C for 3 hours to obtain a blue-black liquid. 1.5 g of cation exchange resin Lewatit Mono plus S108 and 1.5 g of anion exchange resin Lewatit MP 62 were added to the blue-black liquid, stirred for 2 hours, and then filtered to obtain the final product PEDOT-PC:PSS polymer 17, which was stored at 4°C.
[0135] (2) Weigh 1 mL of PEDOT-PC:PSS polymer 17, add it to 0.5 mL of dimethyl sulfate and 0.05 mL of wetting agent DBSA, mix them, and stir them at room temperature in the dark for 600 r min. -1 After 4 h of maintenance, 0.08 mL of crosslinker GOPS was added and ultrasonicated for 5 min, and then 5 mg of glucose oxidase was mixed with a vortex oscillator for 1 min to prepare a multifunctional enzyme-containing ink. The prepared ink was spin-coated or drop-coated on a substrate (spin coating 1500 r min -1The mixture was kept for 45 s) and dried on a hot stage at 50°C for 12 h to obtain a glucose sensor.
[0136] (3) A three-electrode system was used, with a platinum mesh as the counter electrode, Ag / AgCl as the reference electrode, and a glucose sensing electrode as the working electrode. The prepared glucose sensor was stored in 1 mg mL -1 The samples were stored in bovine serum albumin (BSA) for 2 weeks to simulate a complex usage environment and stored at 25°C. The current response to 200 μM glucose was tested and then the relative sensitivity was calculated. The relative sensitivity of PEDOT:PSS was 3.1% and that of our sensing material was 61.7%.
[0137] Embodiment 18
[0138] This embodiment is basically the same as the above embodiment, with the following features:
[0139] In this embodiment, a method for preparing a material formed from enzyme-containing conductive bio-ink comprises the following steps:
[0140] (1) Weigh 184 mg of 30% HPSS aqueous solution in a 10 mL eggplant bottle, add 1 mL of deionized water, and heat at room temperature at 600 r min. -1 Stir for 20 min, weigh 101.2 mg of EDOT-PC from the glove box and dissolve it in 1 mL of deionized water. -1 Stir for 20 min, pour it into HPSS after it is completely dissolved, and heat it at room temperature at 600 r min -1 Stir for 20 min. Weigh 106.6 mg of sodium persulfate as an oxidant and 0.8 mg of ferric sulfate as a catalyst and heat at room temperature at 600 r min -1 Stir for 20 minutes. After it is completely dissolved, add it into the polymer aqueous solution and keep stirring at 400 r min. -1 The mixture was stirred at 30°C for 3 hours to obtain a blue-black liquid. 1.5 g of cation exchange resin Lewatit Mono plus S108 and 1.5 g of anion exchange resin Lewatit MP 62 were added to the blue-black liquid, stirred for 2 hours, and then filtered to obtain the final product PEDOT-PC:PSS polymer 18, which was stored at 4°C.
[0141] (2) Weigh 1 mL of PEDOT-PC:PSS polymer 18, add it to 0.5 mL of erythritol and 0.05 mL of wetting agent DBSA, mix them, and stir them at room temperature in the dark for 600 r min. -1After 4 h of maintenance, 0.08 mL of crosslinker GOPS was added and ultrasonicated for 5 min, and then 5 mg of glucose oxidase was mixed with a vortex oscillator for 1 min to prepare a multifunctional enzyme-containing ink. The prepared ink was spin-coated or drop-coated on a substrate (spin coating 1500 r min -1 The resulting mixture was kept for 45 seconds and dried on a hot stage at 60°C for 12 hours to obtain a glucose sensor.
[0142] (3) A three-electrode system was used, with a platinum mesh as the counter electrode, Ag / AgCl as the reference electrode, and a glucose sensing electrode as the working electrode. The prepared glucose sensor was stored in 1 mg mL -1 The samples were stored in bovine serum albumin (BSA) for 2 weeks to simulate a complex usage environment and stored at 25°C. The current response to 200 μM glucose was tested and then the relative sensitivity was calculated. The relative sensitivity of PEDOT:PSS was 1.4% and that of our sensing material was 71.5%.
[0143] Embodiment 19
[0144] This embodiment is basically the same as the above embodiment, with the following features:
[0145] In this embodiment, a method for preparing a material formed from enzyme-containing conductive bio-ink comprises the following steps:
[0146] (1) Weigh 184 mg of 30% HPSS aqueous solution in a 10 mL eggplant bottle, add 1 mL of deionized water, and heat at room temperature at 600 r min. -1 Stir for 20 min, weigh 101.2 mg of EDOT-PC from the glove box and dissolve it in 1 mL of deionized water. -1 Stir for 20 min, pour it into HPSS after it is completely dissolved, and heat it at room temperature at 600 r min -1 Stir for 20 min. Weigh 106.6 mg of sodium persulfate as an oxidant and 0.8 mg of ferric sulfate as a catalyst and heat at room temperature at 600 r min -1 Stir for 20 minutes. After it is completely dissolved, add it into the polymer aqueous solution and keep stirring at 400 r min. -1 The mixture was stirred at 30°C for 3 hours to obtain a blue-black liquid. 1.5 g of cation exchange resin Lewatit Mono plus S108 and 1.5 g of anion exchange resin Lewatit MP 62 were added to the blue-black liquid, stirred for 2 hours, and then filtered to obtain the final product PEDOT-PC:PSS polymer 19, which was stored at 4°C.
[0147] (2) Weigh 1 mL of PEDOT-PC:PSS polymer 19, add it to 0.5 mL of xylitol and 0.05 mL of wetting agent DBSA, mix them, and stir them at room temperature in the dark for 600 r min. -1 After 4 h of maintenance, 0.08 mL of crosslinker GOPS was added and ultrasonicated for 5 min, and then 5 mg of glucose oxidase was mixed with a vortex oscillator for 1 min to prepare a multifunctional enzyme-containing ink. The prepared ink was spin-coated or drop-coated on a substrate (spin coating 1500 r min -1 The mixture was kept for 45 s) and dried on a hot stage at 40°C for 12 h to obtain a glucose sensor.
[0148] (3) A three-electrode system was used, with a platinum mesh as the counter electrode, Ag / AgCl as the reference electrode, and a glucose sensing electrode as the working electrode. The prepared glucose sensor was stored in 1 mg mL -1 The samples were stored in bovine serum albumin (BSA) for 2 weeks to simulate a complex usage environment and stored at 25°C. The current response to 200 μM glucose was tested and then the relative sensitivity was calculated. The relative sensitivity of PEDOT:PSS was 2.1% and that of our sensing material was 63.2%.
[0149] Embodiment 20
[0150] This embodiment is basically the same as the above embodiment, with the following features:
[0151] In this embodiment, a method for preparing a material formed from enzyme-containing conductive bio-ink comprises the following steps:
[0152] (1) Weigh 184 mg of 30% HPSS aqueous solution in a 10 mL eggplant bottle, add 1 mL of deionized water, and heat at room temperature at 600 r min. -1 Stir for 20 min, weigh 101.2 mg of EDOT-PC from the glove box and dissolve it in 1 mL of deionized water. -1 Stir for 20 min, pour it into HPSS after it is completely dissolved, and heat it at room temperature at 600 r min -1 Stir for 20 min. Weigh 106.6 mg of sodium persulfate as an oxidant and 0.8 mg of ferric sulfate as a catalyst and heat at room temperature at 600 r min -1 Stir for 20 minutes. After it is completely dissolved, add it into the polymer aqueous solution and keep stirring at 400 r min. -1The mixture was stirred at 30°C for 3 hours to obtain a blue-black liquid. 1.5 g of cation exchange resin Lewatit Mono plus S108 and 1.5 g of anion exchange resin Lewatit MP 62 were added to the blue-black liquid, stirred for 2 hours, and then filtered to obtain the final product PEDOT-PC:PSS polymer 20, which was stored at 4°C.
[0153] (2) Weigh 1 mL of PEDOT-PC:PSS polymer 20 and add it to 0.5 mL of DMSO and 0.05 mL of wetting agent DBSA, mix them, and stir them at room temperature in the dark for 600 r min. -1 After 4 h of maintenance, 0.08 mL of crosslinker GOPS was added and ultrasonicated for 5 min, and then 5 mg of glucose oxidase was mixed with a vortex oscillator for 1 min to prepare a multifunctional enzyme-containing ink. The prepared ink was spin-coated or drop-coated on a substrate (spin coating 1500 r min -1 The mixture was kept for 45 s), and dried on a hot stage at 50°C for 24 h to obtain a glucose sensor.
[0154] (3) A three-electrode system was used, with a platinum mesh as the counter electrode, Ag / AgCl as the reference electrode, and a glucose sensing electrode as the working electrode. The prepared glucose sensor was stored in 1 mg mL -1 The samples were stored in bovine serum albumin (BSA) for 2 weeks to simulate a complex usage environment and stored at 25°C. The current response to 200 μM glucose was tested and then the relative sensitivity was calculated. The relative sensitivity of PEDOT:PSS was 0% and that of our sensing material was 27.6%.
[0155] The monomers and structural formulas used in Examples 1-20 are shown in Table 1.
[0156] Table 1. Monomers and structural formulas of various embodiments of the present invention
[0157]
[0158]
[0159]
[0160]
[0161]
[0162] The embodiments of the present invention are described above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various changes can be made according to the purpose of the invention of the present invention. Any changes, modifications, substitutions, combinations or simplifications made according to the spirit and principle of the technical solution of the present invention should be equivalent replacement methods. As long as they meet the purpose of the invention of the present invention and do not deviate from the technical principles and inventive concepts of the present invention, they belong to the protection scope of the present invention.
Claims
1. A conductive bio-ink with solution processability, characterized in that Contains zwitterion functionalized poly 3,4-ethylenedioxythiophene: polystyrene sulfonate, water, additives, 3-glycidyloxypropyltrimethoxysilane (GOPS). The molded material has good conductivity, water phase stability, biocompatibility and anti-fouling properties.
2. The method for preparing a conductive bio-ink with solution processability according to claim 1 is as follows: preparing a zwitterion functionalized 3,4-ethylenedioxythiophene aqueous solution and a styrene sulfonate aqueous solution, adding sodium persulfate as an oxidant and ferric sulfate as a catalyst, stirring at a temperature of 30°C for 3 hours, and post-treating by adding a cation exchange resin and an anion exchange resin to obtain a zwitterion functionalized poly 3,4-ethylenedioxythiophene: polystyrene sulfonate, and then adding an additive for stirring, wherein the additive concentration is 0.01-10 mg mL -1 The stirring time is (3.5-4.5h) and the stirring temperature is (20-30℃). GOPS is added and ultrasonicated for 5min. The GOPS concentration is 0.01-10mg mL -1 .
3. A conductive bio-ink with solution processability according to claims 1 and 2, characterized in that The molar ratio of the zwitterionic functionalized poly (3,4-ethylenedioxythiophene) aqueous solution and styrene sulfonate involved in the reaction is (1:0.5-1:1.5).
4. A solution processable conductive bio-ink according to claims 1, 2 and 3, characterized in that Contains at least one of dimethyl sulfoxide, ethylene glycol, dimethylformamide, tetrahydrofuran, glycerol, sorbitol, ethylene glycol monomethyl ether, diethylene glycol, dimethyl sulfate, erythritol and xylitol additives.
5. A conductive bio-ink with solution processability according to claims 1, 2, 3 and 4, characterized in that the ink is biocompatible and the ink after complexing with an enzyme can maintain a relative enzyme activity of not less than 80% within 30 minutes.
6. A method for preparing conductive bio-ink according to claims 1, 2, 3 and 4 is: depositing the prepared conductive bio-ink on different substrates by printing or other solution processing, and then heating and curing at a specific temperature. It is characterized in that The cross-linking temperature is (40-60°C) and the cross-linking time is (10-14h), so that the molding ink material has both excellent conductivity and water phase stability. The ink has excellent conductivity (greater than 500mS cm -1 ), stored in an aqueous environment without disintegration for more than 2 weeks.
7. The method for preparing a material formed by enzyme-containing conductive biological ink according to claim 6 is characterized in that: The invention also contains at least one of the biological enzymes such as glucose oxidase, glucose dehydrogenase, galactose oxidase, cholesterol oxidase, amino acid oxidase, alcohol oxidase, lactate oxidase, laccase, catalase and uricase.
8. The material formed by the enzyme-containing conductive bio-ink according to claim 7, characterized in that the material has good biocompatibility and the relative enzyme activity is not less than 70% after being stored at room temperature for two weeks.
9. The material formed by the enzyme-containing conductive bio-ink according to claim 7 has good anti-fouling properties and can resist the adhesion of proteins in complex environments to the surface of the material.
10. The material formed by the enzyme-containing conductive biological ink according to claim 7, characterized in that: It can be used to prepare enzyme-based sensors.
